2014
DOI: 10.1177/1525740114539002
|View full text |Cite
|
Sign up to set email alerts
|

Print Knowledge of Preschool Children With Hearing Loss

Abstract: Measures of print knowledge were compared across preschoolers with hearing loss and normal hearing. Alphabet knowledge did not differ between groups, but preschoolers with hearing loss performed lower on measures of print concepts and concepts of written words than preschoolers with normal hearing. Further study is needed in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
2
18
1
1
Order By: Relevance
“…Conceptual print knowledge findings, however, suggest that children with hearing loss perform more poorly than children with normal hearing on this category of print skills. The findings of this study confirm earlier findings of Werfel et al (2015). In addition, children with hearing loss exhibited slower rates of change than children with normal hearing on print concept knowledge.…”
Section: Print Knowledgesupporting
confidence: 89%
See 1 more Smart Citation
“…Conceptual print knowledge findings, however, suggest that children with hearing loss perform more poorly than children with normal hearing on this category of print skills. The findings of this study confirm earlier findings of Werfel et al (2015). In addition, children with hearing loss exhibited slower rates of change than children with normal hearing on print concept knowledge.…”
Section: Print Knowledgesupporting
confidence: 89%
“…However, these studies focused primarily on alphabet knowledge, not print knowledge as a whole. Werfel, Lund, and Schuele (2015) challenged this conclusion of relative strength. For alphabet knowledge, preschool children with hearing loss were at least commensurate with, and in some cases more advanced than, their peers with normal hearing.…”
Section: Print Knowledgementioning
confidence: 99%
“…The reader will note that we have emphasized the relationship between alphabetic knowledge and phonological sensitivity, omitting the print concept knowledge portion of print awareness. We argue that phonological sensitivity may build on alphabetic knowledge in particular due first to the relationship between sound symbols and sound knowledge, and second because print concepts may not be as strong as alphabetic knowledge for children with HL (Werfel et al, 2015). Print concepts may benefit from increases in shared book reading between children with HL and their caregivers (DesJardin et al, 2008), and we anticipate that increases in exposure to print concepts could remediate this deficit.…”
Section: Co-development Of Print Awareness and Phonological Sensitivitymentioning
confidence: 91%
“…A recent study by Werfel et al (2015) expands on our knowledge of print awareness in children with hearing loss, including both CI users and hearing aid users. They observed that the literature to date had focused on children's alphabetic knowledge, but that print awareness is a broader concept that includes print concept knowledge and word concept knowledge (e.g., Justice and Ezell, 2001;Levy et al, 2006).…”
Section: Print Awarenessmentioning
confidence: 99%
“…A small sample of elementary school children with CIs demonstrated no significant differences in real or nonsense word reading compared to hearing peers with matched ageequivalency reading scores (Apel & Masterson, 2015), but a sample of secondary school students demonstrated single word reading abilities approximately 3 years below chronological age (Harris & Terlektsi, 2011). Delays have also been reported among preschool children with hearing aids and CIs in foundational orthographic awareness skills of print knowledge and word concept knowledge (Werfel, Lund, & Schuele, 2015).…”
Section: Orthographic Awarenessmentioning
confidence: 94%